Agglomeration, Population Size, and the Cost of Providing Public Services: An Empirical Analysis for German States - Dan Stegarescu; Robert Schwager; Thiess Büttner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper is concerned with the question as to what extent population size and density affect the cost of providing public services at the subnational level. Empirical estimates of cost functions are obtained from an analysis of the expenditures of German states disaggregated into about 40 functions of government. The empirical results indicate that generally there is no significant relationship between population density and the cost of public goods. At the same time, cost are almost proportionately related to population size indicating that goods and services provided by the German states display only a limited degree of publicness.
Keywords: H73; H72; H41; 330; agglomeration; cost of public services; local public goods; Bevölkerungsdichte; Ballungsraum; Lokales öffentliches Gut; Kosten; Öffentliche Ausgaben; Teilstaat; Schätzung; Deutschland